Neoliberal Dynamics and the Ascent of Far Right Ideologies Among the Global Working Class. The Strange Paradox. - Pinto Tortosa, Antonio Jesús (Palgrave, 2023)
In the 1970s and the 1980s two countries led the promotion of neoliberal economic solutions to conventional issues associated to the nature of capitalism itself. Margaret Thatcher in the United Kingdom, and Ronald Reagan in the United States, championed the export of neoliberal economic reforms, catalogued under the term Structural Adjustment Policies (SAPs), whose goal was to turn countries into profitable destinies for foreign investment, as well as trustworthy money borrowers. SAPs turned into a cross-ideological tool to keep the global economy working, since conservative as well as labor governments had to carry them out. The price to pay for the countries’ economic reliability was an impoverished global working class, who lost acquisitive power and social rights for the sake of a major “common good”. As years went by, workers around the world realized that right wing and left wing governments applied exactly the same economic measures, so they blamed socialist and labor parties for contributing to their pauperization. In the last decade far right political formations have come to fill in the gap that leftist parties left behind, persuading the workers that they are the ones who will actually pay attention to their needs. That is how it is possible to explain the ascent of neo-conservatism and far right political leaders worldwide. Workers, however, do not realize that those parties and leaders actually represent ultra liberal solutions that will only impoverish them even further.
Keywords: Neoliberalismo; Populismo; Neoliberalism; Working Class; Far Right; Populism; SAPs